2013
DOI: 10.1186/1476-511x-12-131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity circuit training, low-intensity circuit training and endurance training on blood pressure and lipoproteins in middle-aged overweight men

Abstract: BackgroundThe aim of this study was to determine the physiological effects of an high-intensity circuit training (HICT) on several cardiovascular disease risk factors in healthy, overweight middle-aged subjects, and to compare the effects of HICT to traditional endurance training (ET) and low-intensity circuit training (LICT).MethodsFifty-eight participants (ages 61±3.3 yrs, BMI 29.8±0.9) were randomly assigned to one of the three exercise treatment groups: HICT, LICT and ET. The three groups exercised three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
138
3
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(157 citation statements)
references
References 54 publications
13
138
3
3
Order By: Relevance
“…We also observed significant differences in the HDL, TC, and HDL/TC post-test values of the two study groups, but there was no significant difference in the LDL, TG, and ApoB values between the two groups. These results are in line with some studies (8,(15)(16)(17) and inconsistent with a few other studies (18)(19)(20). Increased LDL level is an independent risk factor for coronary artery disease, and its reduction to 60 mg/dl will reduce the incidence of coronary artery disease by 50% within two years (21).…”
Section: Discussionsupporting
confidence: 51%
“…We also observed significant differences in the HDL, TC, and HDL/TC post-test values of the two study groups, but there was no significant difference in the LDL, TG, and ApoB values between the two groups. These results are in line with some studies (8,(15)(16)(17) and inconsistent with a few other studies (18)(19)(20). Increased LDL level is an independent risk factor for coronary artery disease, and its reduction to 60 mg/dl will reduce the incidence of coronary artery disease by 50% within two years (21).…”
Section: Discussionsupporting
confidence: 51%
“…It has been proposed that chronic high-intensity interval training (HIIT) (≈85% VO 2max ) may elicit greater health benefits than traditional chronic aerobic exercise. Reasons for this supposition include improvements in SOD activity [11], aerobic capacity [15], blood lipids [16], and blood pressure [17] that are more remarkable when exercise is performed at higher intensities.…”
Section: Introductionmentioning
confidence: 99%
“…Antonio Paoli et al [8] found the effects of high intensity circuit training, low intensity circuit training and endurance training on blood pressure and lipoproteins in middle aged overweight men and the main finding of this study was the greater effect on blood lipids improvement of a high intensity circuit compared to a lighter circuit or to an endurance training. Different kinds of circuit showed different effects on blood pressure.…”
Section: Discussionmentioning
confidence: 74%
“…Low intensity circuit training more improves systolic blood pressure compared to high intensity training and endurance training while the effect of exercise on diastolic blood pressure was greater in response to high intensity circuit training. Resistance training has long been accepted for developing and maintaining muscular strength, endurance, and power and muscle mass [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation